2018
DOI: 10.1088/1361-6595/aaf536
|View full text |Cite
|
Sign up to set email alerts
|

Fluid-model analysis on discharge structuring in the RF-driven prototype ion-source for ITER NBI

Abstract: A 2D self-consistent fluid plasma model is employed for studying the plasma in the radiofrequency (RF)-driven negative hydrogen ion source prototype developed to equip the neutral beam injector systems for ITER. The source is considered in its usual configuration with a cylindrical driver and magnetic filter field (MF) produced by permanent magnets arranged in a magnet frame movable along the expansion chamber. The model accounts for the RF injection, the bias potential applied at the plasma grid (PG) and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(51 citation statements)
references
References 57 publications
0
51
0
Order By: Relevance
“…Modeling efforts, mainly by fluid codes, deepened the insights into the physics behind the vertical plasma drift. It is demonstrated that the drifts are driven by the interplay of the magnetic filter field with gradients of the electron temperature (diamagnetic drift, close to the exit of the RF drivers) and with electric fields (E × B drift, close to the PG) [35]. Simple transport codes as well as particle-in-cell (PIC) code modeling predict that also nonuniformities within the single extracted beamlets can occur [36,37] (see also Beam Extraction and Formation.…”
Section: Parameters Influencing the Uniformitymentioning
confidence: 99%
“…Modeling efforts, mainly by fluid codes, deepened the insights into the physics behind the vertical plasma drift. It is demonstrated that the drifts are driven by the interplay of the magnetic filter field with gradients of the electron temperature (diamagnetic drift, close to the exit of the RF drivers) and with electric fields (E × B drift, close to the PG) [35]. Simple transport codes as well as particle-in-cell (PIC) code modeling predict that also nonuniformities within the single extracted beamlets can occur [36,37] (see also Beam Extraction and Formation.…”
Section: Parameters Influencing the Uniformitymentioning
confidence: 99%
“…The steady-state plasma column is radially unbounded and typically 1.5 m long. It can be conveniently measured in the main vacuum chamber, axially and radially, by using the B-dot probe [134] as shown in Fig. 25.…”
Section: Helicon Waves In Raidmentioning
confidence: 99%
“…A significant effort has been devoted in the past 10 years to model the plasma behavior of fusion type NIS with fluid [134][135][136] and Particle-In-Cell models with Monte-Carlo-Collisions (PIC-MCC) [66,[137][138][139][140]. The latter have been optimized to run on supercomputers via a parallelization of the algorithms using MPI and OpenMP libraries.…”
Section: Latest Improvements In Numerical Modeling Of Negative Ion Sources For Nbimentioning
confidence: 99%
“…Standalone fluid models for the electrons are used to study high plasma density (10 16 − 10 19 m −3 ) discharges at low pressure (< 50 mTorr) [18][19][20] . Altough fluid models under these conditions are compromised by the fact that the electron-electron mean-free path is comparable to the size of the device, the dimensions of the system are often too large for full kinetic simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Instead, most of these multi-fluid models, e.g. [18][19][20] , obtain the closure by taking moments of a kinetic equation with a Bhatnagar-Gross-Krook (BGK) operator for the electronneutral collisions where the collisional frequency is computed as an average rate computed with Maxwellian electrons. As it will be shown in this paper, the resulting system of fluid equations is incomplete (missing effects such as thermal friction or the effect of non-Maxwellian electron energy distribution function (EEDF)) and overestimates the transport coefficients and collisional rates, in particular the ionization and excitation rates.…”
Section: Introductionmentioning
confidence: 99%